2020
DOI: 10.1111/ctr.14050
|View full text |Cite
|
Sign up to set email alerts
|

ABO‐incompatible living kidney transplantation

Abstract: To date, kidney transplantation is the optimal replacement therapy for most patients with end-stage renal disease (ESRD) because of a higher survival rate and decreased cost. 1,2 However, many patients have to undergo dialysis for many years owing to the growing kidney transplantation waiting list and organ scarcity. To overcome the shortage of available organs, various strategies have been established. Apart from increased deceased donor and marginal kidney use, more attention has been focused on expanding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…Moreover, PEX is the less expensive and more widely and rapidly available apheresis technique. 38 , 39 …”
Section: Antibodies Depletion Strategies and Resultsmentioning
confidence: 99%
“…Moreover, PEX is the less expensive and more widely and rapidly available apheresis technique. 38 , 39 …”
Section: Antibodies Depletion Strategies and Resultsmentioning
confidence: 99%
“…Postoperative maintenance immunosuppressants typically involve the use of calcineurin inhibitors (CNIs) combined with mycophenolic acid and glucocorticoids [7]. Some centers are trying new immunosuppressive programs, such as rituximab [8]. Some experimental methods, such as gut microbiota, are also undergoing preclinical research [9].…”
Section: Perioperative Carementioning
confidence: 99%
“…Removal of circulating ABO antibodies: Various methods have been used for decreasing ABO antibodies titer including plasmapheresis, immunoadsorption, double filtration plasmapheresis, and selective plasma exchange[ 23 ]. While the latter showed less adverse effects due to the preservation of essential plasma components, studies showed that single-use of selective plasma exchange was less efficient than unselective immunoadsorption in removing the circulating ABO antibodies[ 24 ].…”
Section: Blood Group Antigens and Kidney Transplantationmentioning
confidence: 99%
“…Malignancy: There is no statistically significant difference in developing malignancy between ABO-I and ABOC groups despite aggressive induction therapy[ 23 , 6 , 47 , 49 ].…”
Section: Blood Group Antigens and Kidney Transplantationmentioning
confidence: 99%